Efficacy and safety of immune checkpoint inhibitors in advanced biliary tract cancer: a real-world study - Zheng, Yichen; Guo, Jiamin; Ren, Tonghui; Ma, Ji; Cao, Dan (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) combined with gemcitabine and cisplatin chemotherapy have become the standard first-line treatment for advanced biliary tract cancer (BTC). However, real-world evidence on domestic ICIs widely used in China and the therapeutic outcomes across treatment lines remains limited. This study aimed to assess the real-world effectiveness and safety profiles of ICIs in advanced BTC patients, while concurrently elucidating potential efficacy variations among distinct ICI subtypes.MethodsWe analyzed patients with unresectable, locally advanced, or metastatic BTC treated with ICIs at West China Hospital (January 2019–October 2023). Primary endpoint was overall survival (OS), while secondary endpoints included progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and safety. Kaplan-Meier survival curves, propensity score matching (PSM), and Cox proportional hazards regression analyzed treatment efficacy.ResultsA total of 221 advanced BTC patients were enrolled. Among them, 137 patients received ICIs treatment in the first line, while 84 patients in the second or later lines. For patients treated with ICIs as first-line therapy, the median OS was 15.7 months (95% CI: 13.1-19.8) and PFS was 8.4 months (95% CI: 7.6-10.3). In contrast, patients treated in second or later lines had shorter median OS of 9.8 months (95% CI: 8.1–12.3) and median PFS of 5.6 months (95% CI: 4.2–6.8). The reduced efficacy in later-line treatments may reflect prior therapeutic resistance and generally poorer patient conditions compared to first-line recipients. 211 (95.5%) patients experienced at least one adverse event (AE), and 93 (42.1%) of them experienced grade 3 or higher AEs. The incidence of immune-related adverse events (irAEs) was 35.8%, with 8.6% of patients experiencing grade 3-4 irAEs. The most common ICI treatments are with Durvalumab or Sintilimab, which we are interested in comparing. Durvalumab showed numerically superior OS vs Sintilimab (19.3 vs 10.2 months, p<0.001) in unmatched analysis, though significance attenuated after PSM (16.1 vs 13.1 months, p=0.299).ConclusionICIs demonstrate robust efficacy and manageable toxicity in real-world settings, supporting their use in both first- and later-line treatments for advanced BTC. However, whether domestic ICI alternatives remain viable options warranting further validation.